Private sector development and competitiveness in Ghana - Susanna Wolf (University of Bonn, Center for Development Research (ZEF), 2003)
Ghana has a relatively good international reputation with respect to political stability and macroeconomic reforms. However, its success with developing the private sector and attracting investment has at best been mixed. Therefore the new government that came into power in 2001 proclaimed a Golden Age of Business. Competitiveness and private sector development are closely interlinked. On the one hand the factors that influence the competitiveness of a country are a precondition for private sector development. On the other hand only if the private enterprises act in a competitive manner and use their entrepreneurial possibilities to compete, support programmes for the private sector will be successful. Competitiveness can be measured at different levels. The real exchange rate covers the competitiveness of a whole economy, it fluctuated significantly in Ghana over the past decade. The revealed comparative advantage index and value added per employee explore the relative competitiveness of different sectors. Especially for plastic and metal products they both show that Ghana is increasingly competitive.
Keywords: 330; Political Economy; Privatwirtschaft; Wirtschaftspolitik; Investitionspolitik; Branche; Internationaler Wettbewerb; Ghana